First comprehensive report of bacteria spp. associated with cloaca of Laudakia nupta (Sauria: Agamidae) in Iran using molecular studies - Farkhondeh Sayyadi (Laboratory Animal Research, 2019)
Abstract Iran bears a remarkable variety of reptiles. One of the lizard families occurring in Iran is the Family Agamidae which is widely are distributed throughout the old world. The large-scaled rock agamid, Laudakia nupta, is one of the well-known agamid. There are few reports of cloacal microbial on reptiles hence their function in cloacae remains unknown. Laudakia nupta usually live in rural and urban areas and close vicinity to man, they are likely to play an important role in the spread of disease that may be caused by these microorganisms and their transmission to man. Therefore, the aim of this study was to identify the bacterial flora colonizing the cloacal region of Laudakia nupta using molecular studies. The cloacal fluids were directly placed on nutrient agar (NA) plates and incubated at 25 ± 2 °C for 48 h. The resulting bacterial colonies were transferred to fresh nutrient agar (NA) plates for molecular studies. Twelve isolates were obtained from 17 specimens of Laudakia nupta. All bacteria isolates were identified as Bacillus subtillis (5), Bacillus cereus (4), Bacillus sp. (1), Pseudomonas putida (1), and Pseudomonas sp. (1) based on partial sequences of the 16 s rRNA gene. This is the first comprehensive report of bacteria spp. associated with cloaca of Laudakia nupta using molecular studies. In this research, we found that Laudakia nupta can be a carrier of bacteria which can transfer microorganisms to hosts.